2022
DOI: 10.3390/molecules27072302
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Properties of Medicinal Mushrooms and Their Bioactive Compounds for the COVID-19 Era—An Appraisal: Do the Pro-Health Claims Measure Up?

Abstract: Many mushroom species are consumed as food, while significant numbers are also utilised medicinally. Mushrooms are rich in nutrients and bioactive compounds. A growing body of in vitro, in vivo, and human research has revealed their therapeutic potentials, which include such properties as anti-pathogenic, antioxidant, anti-inflammatory, immunomodulatory, gut microbiota enhancement, and angiotensin-converting enzyme 2 specificity. The uses of medicinal mushrooms (MMs) as extracts in nutraceuticals and other fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…It is not easily obtained in pure form (though biotechnological processes are starting to make it [ 808–817 ]), but its availability via mushrooms can provide a convenient supply [ 818–820 ]. Indeed mushrooms themselves have been shown to be highly protective against mild cognitive impairment [ 821 ], as well as other diseases involving oxidative stress [ 787 ], and are themselves under consideration and trial as anti-COVID-19 agents [ 822 , 823 ].…”
Section: Anticoagulants Platelet Inhibitors and The Triple Treatmentmentioning
confidence: 99%
“…It is not easily obtained in pure form (though biotechnological processes are starting to make it [ 808–817 ]), but its availability via mushrooms can provide a convenient supply [ 818–820 ]. Indeed mushrooms themselves have been shown to be highly protective against mild cognitive impairment [ 821 ], as well as other diseases involving oxidative stress [ 787 ], and are themselves under consideration and trial as anti-COVID-19 agents [ 822 , 823 ].…”
Section: Anticoagulants Platelet Inhibitors and The Triple Treatmentmentioning
confidence: 99%
“…Presently, there is growing attention on using mushrooms in the development of natural functional dietary supplements and biotherapeutics, as they may modulate the immune system and act as anti-inflammatory through their high content of antioxidants ( 24 , 25 ).…”
Section: Nutritive Value Of Mushroomsmentioning
confidence: 99%
“…Numerous previous studies have demonstrated mushrooms as exhibitors of potential antiviral efficacy, including human exposure to the SARS-CoV-2 virus ( 24 , 107 ).…”
Section: Antiviral Properties Of Mushroomsmentioning
confidence: 99%
“…Mushrooms are the only source of pre- and pro-vitamin Ds in which other bioactives, such as polysaccharides, terpenes, β-glucans, ergothioneine, lectins, polyphenols, etc., are also present; this makes them a unique natural source of valuable bioactives with various activities, including immunostimulant, immunomodulating, antiviral, anticancer, and antidiabetic activity [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Studies by Rangsinth et al (2021) and Elhusseiny et al (2022) have indicated the efficacy of different mushroom bioactives against the main protein of SARS-CoV-2 [ 9 , 24 ].…”
Section: Introductionmentioning
confidence: 99%